Geographical Evaluation of Functional Regional of Koya University (2014-2017) (Raparin Journal of Humanities (RJH), 2022)
The main purpose of this research is to analyze the university of Koya duty region, and the importance of this research is that it will be a road map for the planning and development of  Koya University region, and at the same time it will be clear to us The university has served different areas. In this research, we have relied on the use of the number of students received at the level of administrative institutions to determine the region of the University of Koya duties. For this purpose, the study hypothesizes that the research area has an important geographical position and location, and the university has developed extensively, and also assumes that the scope of koya university's job is as an administrator. In order to achieve the goal of the study, the researcher used regional research, analysis and comparison methods based on the number of students based on their geographical location.    At the end of the study, it concluded that the university's job region crosses the administrative boundaries of  Koya district in most facalities, crossing the Kurdistan region and Iraq at the university's faculty level, and the degree of this effect varies from one region to another.